Answer:
y=sin(ln(x))
Explanation:
First, we have to order the terms as follows and express y' as dy / dx:
![x*(dy)/(dx) =\sqrt{(1-y^(2) )} \\(x)/(dx)=\frac{dy}\sqrt{(1-y^(2) )}}\\(dx)/(x)=\frac{dy}{\sqrt{(1-y^(2) )} }](https://img.qammunity.org/2020/formulas/mathematics/college/hgdnpi01qgkfe2a8uzhzbxw62mmpns0dh7.png)
Then, we have to integrate
![\int{(dx)/(x)=\int{\frac{dy}{\sqrt{(1-y^(2) )} }](https://img.qammunity.org/2020/formulas/mathematics/college/6x4ccijr4dcuby04sn1swez9c0b516uecq.png)
with this solution after integration:
![ln(x)+C1=arcsin(y)+C2](https://img.qammunity.org/2020/formulas/mathematics/college/1ea9jc50eklbvwwd411low1ddoa7nc6i2y.png)
Then, we have to reorder
![arcsin(y)=ln(x)+C](https://img.qammunity.org/2020/formulas/mathematics/college/xl5zv2tbwy93s4hqoxsm09796nequ6unx7.png)
and applied Sin function on both sides
![sin(arcsin(y))=sin(ln(x)+C)\\y=sin(ln(x)+C)](https://img.qammunity.org/2020/formulas/mathematics/college/pixoly66hyb40k2wzl7zwbtiayhxhhdtou.png)
To define the value of C, we use the known point y(1)=0 and replace in the equation
![y=sin(ln(x)+C)\\0=sin(ln(1)+C)\\0=sin(0+C)\\0=sin(C)\\C=arcsin(0)\\C=0](https://img.qammunity.org/2020/formulas/mathematics/college/bzi9c16ec9ucu5vz6rfcnfux3n9p6ih1ev.png)
The function that proves that differential equation is
![y=sin(ln(x))](https://img.qammunity.org/2020/formulas/mathematics/college/4po9ewhrxbgh843lgi4r85fkmyohj4z3or.png)